2005
DOI: 10.1143/jjap.44.2626
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowires as pH Sensor

Abstract: Silicon nanowires (SiNWs) have been used as the sensing layer in an extended gate field effect transistor (EGFET) for the measurement of pH solutions. The SiNWs were synthesized directly from the silicon substrates via a catalytic reaction under N 2 atmosphere at 955 o C without supplying any gaseous or liquid Si sources. Nickel catalyst was deposited on the silicon substrates by sputtering. The average diameter of the SiNWs was about 30 ~ 50 nm and a length of up to a few tens of micrometers. In this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Bashir and co-workers [69] described silicon nanowire oxygen sensor that was realized using top-down microelectronics processing techniques. Unlike the idea of Lieber's group, Hsu et al [70] presented a SiNWbased pH sensor in an extended-gate field-effect transistor. They suggested that SiNWs could support a three-dimensional contact mode, resulting in a larger total surface area, and the SiNWs were cylindrical, which caused the non-bridging Si O bonds of the surface to be of the suspended and standing types.…”
Section: Silicon Nanowire Nanosensorsmentioning
confidence: 99%
“…Bashir and co-workers [69] described silicon nanowire oxygen sensor that was realized using top-down microelectronics processing techniques. Unlike the idea of Lieber's group, Hsu et al [70] presented a SiNWbased pH sensor in an extended-gate field-effect transistor. They suggested that SiNWs could support a three-dimensional contact mode, resulting in a larger total surface area, and the SiNWs were cylindrical, which caused the non-bridging Si O bonds of the surface to be of the suspended and standing types.…”
Section: Silicon Nanowire Nanosensorsmentioning
confidence: 99%
“…Quasi-one dimensional semiconductor nanowires feature a high surface-to-volume ratio and special electronic and optical properties, arising from the size confinement in the nano-sized channel region [1][2][3][4]. These unique aspects, especially in silicon nanowires (SiNWs), stimulate enormous research efforts to design and develop a new generation of high performance FET transistors and sensors by incorporating the SiNWs as the functional channels.…”
Section: Introductionmentioning
confidence: 99%
“…1͒ and oxide-assisted growth ͑Ref. 2͒ modes, and serve as the key elements for high performance SiNWsbased transistors, 3,4 biosensors, 5,6 and energy harvesting devices. 7,8 Recently, we reported an in-plane solid-liquidsolid ͑IPSLS͒ growth mode for fabricating lateral SiNWs in a plasma-enhanced chemical-vapor deposition ͑PECVD͒ system during an all-in situ process.…”
mentioning
confidence: 99%